Effect of Different Concentration of SCOBY Kombucha as an Anti-acne Against Staphylococcus aureus in The Ear of Mice (Mus musculus) - Anggun Putri Ferdyanti; Eva Agustina; Hanik Faizah; Risa Purnamasari (Biology, Medicine, & Natural Product Chemistry, 2025)
SCOBY (Symbiotic Culture of Bacteria and Yeast) results from symbiosis between yeast and bacteria during fermentation. SCOBY kombucha gel combined with orange peel extract has antibacterial compounds that can inhibit the growth of S. aureus bacteria. The method in this study was to make variations in the concentration of SCOBY in the gel and inject S. aureus bacteria into the ears of mice. After 2x24 hours, the diameter of the inflammation caused was observed and SCOBY kombucha gel was applied (0%, 2%, 4%, 8%, 10%, and 12%), positive control (Mediclin 1%), and negative control (without gel application). The results showed that the higher the concentration of SCOBY, the faster the healing activity of the gel against S. aureus. SCOBY kombucha gel has the fastest healing activity in inhibiting acne pathogen S. aureus 12% SCOBY gel. Inflammation in the ears of mice treated with 12% SCOBY gel had healed by the 90th hour, while in other groups of mice it had only healed at the last observation hour, namely the 114th hour.